Medical Rehabilitation of Glioblastoma Multiform: Case Report - Tanti Ajoe K; Martin M (Indonesian Journal of Physical Medicine & Rehabilitation, 2018)
Introduction: Glioblastoma Multiform (GBM) is the most common malignant primary brain tumor. Early rehabilitation program is needed to increasing the independency and the quality of life.Methods: Case presentation of a woman, age 31 years, diagnosed with GBM. Subject has chronic headache by visual analog scale (VAS) was 5 to 6 and progressive of vision loss (0/0), short and intermediate memory loss, the average of limb strength by manual muscle test were four, and immobilization on bedsince one and half year. The first day after craniotomy, patient has Rehabilitation Program; cryotherapy for decreased the pain, therapeutic exercise, and cognitive stimulation exercise for 5 week.Results: After 5 weeks of rehabilitation program, patient has reduced the pain measured by VAS was 0, improved the memory, and be able to ambulationConclusion: Patient post GBM post craniotomy need to have comprehensive rehabilitation program to reduce pain, improve memory and ambulation.Keywords: Glioblastoma Multiform, Rehabilitation Medicine Program